2007
DOI: 10.1038/nature06280
|View full text |Cite
|
Sign up to set email alerts
|

Neural mechanisms mediating optimism bias

Abstract: Humans expect positive events in the future even when there is no evidence to support such expectations. For example, people expect to live longer and be healthier than average, they underestimate their likelihood of getting a divorce, and overestimate their prospects for success on the job market. We examined how the brain generates this pervasive optimism bias. Here we report that this tendency was related specifically to enhanced activation in the amygdala and in the rostral anterior cingulate cortex when i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

50
465
6
20

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 591 publications
(541 citation statements)
references
References 24 publications
50
465
6
20
Order By: Relevance
“…The hippocampus encodes information relative not only to past events but also to future ones [153]. The amygdala is involved in representing future positive events [146]. From this evidence the following question follows: Can hippocampus and amygdala dysfunctions relate in difficulties representing future food intake and steady decisionmaking related to future food intake?…”
Section: Outstanding Questionsmentioning
confidence: 99%
“…The hippocampus encodes information relative not only to past events but also to future ones [153]. The amygdala is involved in representing future positive events [146]. From this evidence the following question follows: Can hippocampus and amygdala dysfunctions relate in difficulties representing future food intake and steady decisionmaking related to future food intake?…”
Section: Outstanding Questionsmentioning
confidence: 99%
“…Although most investigations of unrealistic optimism have taken place within a social-psychological framework, recently there has been growing interest in relevant neural and pharmacological mechanisms (Sharot et al, 2007(Sharot et al, , 2012a(Sharot et al, , 2012b. In a seminal study, Sharot et al (2011) identified right inferior frontal gyrus (IFG), putatively extending into the pars opercularis, as the region of the brain responsible for coding information that should reduce positive expectations; moreover, these authors demonstrated that unrealistic optimism is associated with deficient coding of such information in this region.…”
Section: Introductionmentioning
confidence: 99%
“…Mathematical expectations of the future that are based on an objective evaluation of what is likely to occur, and hopes for the future that are not based on an objective evaluation, yet motivate current choices 3 (Sharot et al, 2007). One's expectations and hopes, however, may not be realized and may be based on achieving identities that while discerned are not consistent with his essence.…”
Section: The Modelmentioning
confidence: 99%